The Cambridge introduction to narrative - Abbott, H. Porter (Cambridge introductions to literature., 2008)
What is narrative? How does it work and how does it shape our lives and the texts we read? H. Porter Abbott emphasizes that narrative is found not just in literature, film, and theater, but everywhere in the ordinary course of people's lives. This widely used introduction, now thoroughly revised, is informed throughout by recent developments in the field and includes two new chapters. With its lucid exposition of concepts and suggestions for further reading, this book is not only an excellent introduction for courses focused on narrative but also an invaluable resource for students and scholars across a wide range of fields, including literature and drama, film and media, society and politics, journalism, autobiography, history, and still others throughout the arts, humanities, and social sciences.